Association between baseline levels of muscular strength and risk of stroke in later life: The Cooper Center Longitudinal Study - Stephen W. Farrell; David Leonard; Qing Li; Carolyn E. Barlow; Kerem Shuval; Jarett D. Berry; Andjelka Pavlovic; Laura F. DeFina (Elsevier, 2024)
Background: Muscular strength is an important component of physical fitness. We evaluated the relationship between baseline muscular strength and risk of stroke among adults who were aged ≥65 years during follow-up. Methods: We included 7627 healthy adults (mean age = 43.9 years, 86.0% male) underwent a baseline physical examination between 1980 and 1989. Muscular strength was determined by 1-repetition maximum measures for bench press and leg press and categorized into age- and sex-specific tertiles for each measure. Cardiorespiratory fitness (CRF) was assessed via a maximal treadmill exercise test. Those enrolled in fee-for-service Medicare from 1999 to 2019 were included in the analyses. Associations between baseline strength and stroke outcomes were estimated using a modified Cox proportional hazards model. In a secondary analysis, we examined stroke risk by categories of CRF where Quintile 1 = low, Quintiles 2-3 = moderate, and Quintiles 4-5 = high CRF based on age and sex. Results: After 70,072 person-years of Medicare follow-up, there were 1211 earliest indications of incident stroke. In multivariable analyses, the hazard ratio (95% confidence interval (95%CI)) for stroke across bench press categories were 1.0 (referent), 0.96 (0.83-1.11), and 0.89 (0.77-1.04), respectively (p trend = 0.14). The trend across categories of leg press was also non-significant (p trend = 0.79). Adjusted hazard ratio (95%CI) for stroke across ordered CRF categories were 1.0 (referent), 0.90 (0.71-1.13), and 0.72 (0.57-0.92) (p trend < 0.01). Conclusion: While meeting public health guidelines for muscular strengthening activities is likely to improve muscular strength as well as many health outcomes in older adults, performing such activities may not be helpful in preventing stroke. Conversely, meeting guidelines for aerobic activity is likely to improve CRF and lower stroke risk.